De legendarische Vincent Hilhorst - Janssen, Leo 1948- (Laren Van Wĳland, 2002)
Vincent, son of hospital porter and legendary city councillor Piet Hilhorst, suffered brain damage in his early childhood due to a failed smallpox vaccination. With much love from his parents, brothers and sisters, Vincent fought his way through life and cherished only one wish: a pilgrimage on foot to Santiago de Compostela in north-west Spain to be overwhelmed by the botafumeiro, the huge censer, which rumbles over the heads of pilgrims in St James' Cathedral.Leo Janssen, a journalist, met Vincent Hilhorst when he was appointed as councillor. They became close friends in a short time. For the Laarder newspaper De Bel, Janssen kept track of Vincent's progress. They both walked their journeys that way. Vincent mostly on foot and Leo often from behind his computer. 'The legendary Vincent Hilhorst ' is a straightforward account using diary excerpts, newspaper articles and photos. "Now you have to do it alone," said youngest brother Marcel, owner of the pancake stand, on Vincent's departure from his parents' house on Barbiersweg in Laren. It became the trip of a lifetime. Lonely in the Netherlands, wandering through Belgium and wandering in France, the turnaround came at the start of the Saint-Jacques Route in Saint Jean Pied de Port. Weeping, he embraced the statue of St James after 99 days. Two weeks later, the Laren pilgrim was welcomed into the village like a true prodigal son.
Travel account of 'the pilgrim' from Laren
Keywords: Travel; Laren (Netherlands); Santiago de Compostela (Spain)